SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF ALUMINIUM OXIDE NANOPARTICLES - D., Manyasree; P., Kiranmayi; S. N., Ravi Kumar R. V. S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: In the present study, synthesized alumina (Al2O3) nanoparticles were characterized and their antibacterial activity against gram positive and gram negative organisms were studied. Methods: The synthesis was carried out by coprecipitation method using aluminium sulfate and NaOH as precursors. The synthesized aluminium oxide nanoparticles were characterized by using X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FT-IR) and scanning electron microscope (SEM) with Energy Dispersive X-ray Analysis (EDX) techniques. Besides, this study determines the antibacterial activity and minimum inhibitory concentration (MIC) of Al2O3 nanoparticles against gram-positive (Staphylococcus aureus and Streptococcus mutans) and gram-negative (E. coli and Proteus vulgaris) bacteria. Results: The average crystallite size of Al2O3 nanoparticles was found to be 35 nm by X-ray diffraction. FT-IR spectrum exhibited the peaks at 615 and 636 were assigned to the aluminium oxide stretching. The EDX measurements indicated the presence of Al along with O peaks. It indicates the purity of the sample. The antimicrobial assay revealed that E. coli showed a maximum zone of inhibition (39 mm) at 50 mg/ml concentration of Al2O3 nanoparticles. Conclusion: In conclusion, aluminium oxide is a good antibacterial agent against both gram positive and gram-negative organisms.